Zastosowanie regresji logistycznej do analizy danych wielomianowych dotyczących samooceny zdrowia mieszkańców Torunia - Kozyra, Cyprian (Application of Logistic Regression to Analysis of Perceived Health Multinomial Data, 2005)
The paper presents application of cumulative logit model to the analysis of multinomial data received from state of health research of Torun inhabitants. Logistic regression models have been used to test the dependence of perceived health assessment on demographic characteristics like age, income and education. Proportional odds model with equal slopes for each category were compared with null independence model and full model with regression coefficients estimated for each category. The following statistical relationships between perceived health and demographic characteristics of respondents were shown in the paper:- the older respondent the poorer perceived health- the more earning respondent the better perceived health,- the longer education the better perceived health.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 319-329